Microbial Ligand Costimulation Drives Neutrophilic Steroid-Refractory Asthma. - Sabelo Hadebe; Frank Kirstein; Kaat Fierens; Kong Chen; Rebecca A Drummond; Simon Vautier; Sara Sajaniemi; Graeme Murray; David L Williams; Pierre Redelinghuys; Todd A Reinhart; Beth A Fallert Junecko; et al. (PLoS ONE)
Asthma is a heterogeneous disease whose etiology is poorly understood but is likely to involve innate responses to inhaled microbial components that are found in allergens. The influence of these components on pulmonary inflammation has been largely studied in the context of individual agonists, despite knowledge that they can have synergistic effects when used in combination. Here we have explored the effects of LPS and β-glucan, two commonly-encountered microbial agonists, on the pathogenesis of allergic and non-allergic respiratory responses to house dust mite allergen. Notably, sensitization with these microbial components in combination acted synergistically to promote robust neutrophilic inflammation, which involved both Dectin-1 and TLR-4. This pulmonary neutrophilic inflammation was corticosteroid-refractory, resembling that found in patients with severe asthma. Thus our results provide key new insights into how microbial components influence the development of respiratory pathology.